Kualitas Lulusan Program Studi Pendidikan Teknik Mesin Universitas Palangka Raya Dalam Dunia Usaha/Industri - Wiyogo Wiyogo; Ahmad Eko Suryanto; Galfri Siswandi; Supriyadi Supriyadi; Vincensius Golderiawan (FKIP Universitas Palangka Raya, 2022)
This study aims to describe the assessment of alumni users on graduate competencies, so as to find out what attributes are considered important that graduates of Mechanical Engineering Education at the University of Palangka Raya should have, then find out what recommendations for improvement can be given to education providers. The results showed that the biggest gap of the five skill levels was the skill level of keyboard competency with a percentage of only 68% with the achievement value only reaching 17 of the target value of 25. The second gap at the enterprise level and entrepreneurial skills only reached a percentage of 78% with an achievement value of only 19.5 from the target value of 25. There are three skills that get a fairly good percentage of scores, such as interpersonal skills. Skills achieve an achievement percentage of 89% or with an achievement value of 35.5. of the target value of 40, at this level it is the highest. Skill management skill level ranks second, with a percentage of 87% with an achievement value of 39 of the target value of 45, and communication skills ranks third with the best achievement, with a percentage of 83%, has an achievement value of 50 of the target value of 60.